2020
DOI: 10.7717/peerj.10491
|View full text |Cite
|
Sign up to set email alerts
|

Plasma BCAA concentrations during exercise of varied intensities in young healthy men—the impact of endurance training

Abstract: Background Branched-chain amino acids (BCAA) i.e., leucine (Leu), isoleucine (Ile) and valine (Val) are important amino acids, which metabolism play a role in maintaining system energy homeostasis at rest and during exercise. As recently shown lowering of circulating BCAA level improves insulin sensitivity and cardiac metabolic health. However, little is known concerning the impact of a single bout of incremental exercise and physical training on the changes in blood BCAA. The present study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Moreover, circulating kynurenine, a tryptophan catabolite is mechanistically influenced by physical activity, with studies reporting exercise-induced kynurenine pathway modulations in both animal and human populations [ 59 ]. Of note, a wide variety of studies have reported significant associations between physical activity and alterations in the levels of plasma metabolites related to BCAA metabolism [ 20 , 21 , 28 , 29 , 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, circulating kynurenine, a tryptophan catabolite is mechanistically influenced by physical activity, with studies reporting exercise-induced kynurenine pathway modulations in both animal and human populations [ 59 ]. Of note, a wide variety of studies have reported significant associations between physical activity and alterations in the levels of plasma metabolites related to BCAA metabolism [ 20 , 21 , 28 , 29 , 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…But there are far fewer metabolomics-based studies focused on physical activity in adolescents and young adults. Two small intervention studies examined short-term exercise-induced physiologic effects on the metabolome of young adults [ 27 , 28 ] while one study explored longitudinal associations of physical activity and serum circulating amino acids concentration in peripubertal girls [ 29 ]. In the present study, we explore potential associations of habitual leisure time physical activity (LTPA) with the plasma and urine metabolome in adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites produced in the body due to exercise may follow the blood transport and act on the adipose tissue, which is our speculation and needs further studies to confirm it. High‐intensity cycling endurance training significantly increased BCAAs metabolism and decreased plasma BCAAs levels compared to the non‐exercised group (Gawedzka et al, 2020). In another study, five regularly trained men exercising for 2 h on power bikes showed a significant increase in plasma BCAAs levels only after long and low intense exercise (Wagenmakers et al, 1989).…”
Section: Molecular Mechanisms Of Exercise‐regulated White Adipocyte D...mentioning
confidence: 99%
“…In fact, a recent study indicates that myocardial accumulation of BCAAs is required for cardiomyocyte hypertrophy and is mediated in part by the coordination of glucose and BCAA utilization in the heart through Kruppel-like factor 15 (Klf15) to promote hypertrophic signaling [ 67 •]. While circulating levels of BCAAs are dependent on exercise intensity [ 68 , 69 ], myocardial abundance of BCAAs have been shown to increase following a bout of exercise but return to normal levels within 24 h [ 33 •]. Interestingly, provision of a diet high in BCAAs for just 4 h at the end of the active phase leads to significant cardiac growth and hypertrophy of cardiomyocytes in mice [ 70 •], which indicates that increases in cardiac BCAA abundance could be an important regulator of cardiac growth.…”
Section: What Are Metabolic Determinants Of Exercise-induced Cardiac ...mentioning
confidence: 99%